Fiqh hibah work on the grounds of judges in the Selangor Shariah Court of appeal - Lateh, Najahudin; Ngatiman, Shanizah; Abbas, Mohd Saleh; Ismail, Albert Feisal @ Muhd Feisal; Abenoh, Nazrul Aini; Mohamad Lutpi, Normarlina; Abu Bakar, Marina (ResearchTrentz Academy Publishing Education Services, 2022)
Grounds of Judgment (GoJ) is something that needs to be done by the Honorable Judge (HJ) based on the facts of the court proceedings after making a decision. This is also implemented in the Shariah Court of Appeal (MRyS) of all states in Malaysia, including in Selangor which covers all cases, including hibah cases. However, is the GoJ based on contradictory and authoritative sources of sharia arguments, especially based on the texts of fiqh works by great classical scholars? If so, what are the works and what are the main issues raised in the judgment. Therefore, this study selects hibah -related cases, namely nine cases as a sample whose primary data was obtained from the Selangor MRyS office. The GoJ data were analyzed descriptively using content analysis methods with inductive, deductive and comparative processing. The results of the study showed that there were seven cases of the HJ based on judgments on 12 texts from eight works of great scholars of the past covering the four major sects of Islam. There are two main issues mentioned, namely (i) general issues related to the pillars and conditions of hibah and (ii) specific issues related to al-Qabd and ownership of hibah items. This study shows that the reasons given when making the decision are contradictory, authoritative and based on shariah facts. The results of this study can be used to improve the governance performance of Shariah Courts and the reference of other researchers.